Resurgence of coups in West Africa and Sahel Alliance implications - Violet. E. Atufe-Musa; Franklins. A. Sanubi; Abraham. E. Orhero (Qualitative Research of Business and Social Sciences, 2025)
The paper, titled "Resurgence of Military Coups in the West African Sub-region and the Implications of the Emergence of the Alliance of Sahel States (AES)," focuses on the military coups in Mali, Burkina Faso, and Niger between 2020 and 2023. These coups constitute disturbing political events that raise serious concerns about political stability in the junta States and the region as a whole. Most importantly, it threatens the future of democratic governance in the West African Sub-region. The aftermath of sanctions on Mali, Burkina Faso and Niger by Economic Community of West Africa States (ECOWAS) and the threat of military intervention amongst other factors gave impetus to the formation of the contending bloc; Alliance of Sahel States (AES) in the region thus leading to fragmentation of the union of ECOWAS, divisive politics, regional economic sabotage by AES member States amongst other unfolding implications. The paper addresses this issue by setting two objectives for the study: to identify the factors underlying recent coups and to examine the impact of the AES on ECOWAS. The State fragility theory was adopted as a framework for the study. The research is qualitative; accordingly, a historical research design was adopted. Findings reveal that though the AES is founded on grounds of addressing rising insecurity amongst its members, the bloc also serves as a tool for legitimizing these junta governments. Also, existing regional cooperative security frameworks and trade liberalization are threatened. The paper recommends that the ruling elite prioritize a sincere and committed focus on enhancing democracy and, by extension, promoting good governance, and that ECOWAS adopt a systemic approach to curtail rising insecurity in the region to facilitate trade and investment. At the same time, continued diplomatic engagement should be used to win back estranged members